PENERAPAN AKHLAK ISLAMI SEBAGAI PILAR ETIKA BISNIS DALAM KEWIRAUSAHAAN - Rizky Fauzi, Abiseka Sahal (Taksasila Edukasi Insani, 2024)
Using Islamic morals as the basis for business ethics in entrepreneurship to address issues such as cheating and exploitation. Business with integrity and sustainability is based on the principles of honesty, trustworthiness and justice. To examine the application of these values, this research uses a qualitative literature study methodology. The results show that honesty fosters consumer trust, trustworthiness guarantees that high-quality products will be accountable, and justice makes the workplace fair. By incorporating these Islamic moral values, businesses gain a better reputation and build beneficial relationships with each other.Keywords : Islamic morals, business ethics, entrepreneurship, honesty